Gate Driver Circuit of Power Electronic Switches with Reduced Number of Isolated DC/DC Converter for a Switched Reluctance Motor - Ali Asghar Memon; Imtiaz Hussain; Muhammad Aslam Uqaili (Mehran University Research Journal of Engineering and Technology, 2013)
This paper presents a gate driver circuit for the switching devices used in the asymmetrical converter for a switched reluctance machine with reduced number of isolated dc/dc converters. Isolation required in the gate driver circuit of switching devices is indispensable. For the purpose of isolation different arrangements may be used such as pulse transformers. The dc/dc converter for isolation and powering the gate drive circuits is suitable, cheaper in cost and simple to implement. It is also significant that required number of isolation converters is much less than the switches used in converter. In addition, a simple logic circuit has been presented for producing the gate signals at correct phase sequence which is compared with the gated signals directly obtained from the encoder of an existing machine.